Modification of Chitosan-Chitosan Phtalate Anhydrides Matrices - Atmaja, Lukman; Manimoy, Herianus; Arizka, Lina Eka (IPTEK The Journal for Technology and Science, 2025)
Chitin and chitosan are natural biopolymers found on shrimp shells. Chitosan is used extensively as a raw material in various industries. The study aimed to extract chitin and chitosan from fanami shrimp skin through deproteinization, demineralization, and deacetylation reactions and to modify the matrix to improve the physical properties. The results of the analysis of the FTIR chitin spectrum show several major peaks at wave number 3446.91 inverse centimeters which indicate vibrations of bending secondary amide and amine (NH) secondary amides at 1654.98 inverse centimeters indicating the presence of CH stretching vibrations. The results of the chitosan FTIR spectrum analysis show symmetrical stretching vibrations at 3433.41 inverse centimeters due to overlapping OH and amines (NH), stretching vibrations at 1653.05 inverse centimeters caused by the propagation of carbon-oxygen double bond stretching, and stretching vibrations at 1587.47 inverse centimeters indicating secondary amide. The results of the characterization with X-ray diffraction (XRD) show that the extracted compounds were chitin and chitosan. In modifying the chitosan matrix, the spectra result shows a peak at 1656.91 to 1564.32 inverse centimeters indicating the presence of an amide group. A new aromatic group peak was found in the area of 1631.83 inverse centimeters which was not found in chitosan. The diffractogram from pure chitosan shows three highest peaks at two theta equal to 609.2, 609.88, and 550 degrees, while chitosan-anhydrous modification shows a peak at two theta equal to 609.8 degrees. The addition of anhydrous phthalates to chitosan has reduced its crystallinity which results in an increase in the hydrophilic characteristics of the membrane. The results of this study are expected to be one of the references in further research regarding the manufacture of phthalate chitosan-anhydrous based composite membranes for direct methanol fuel cells.